VD_FINDINFO Décision / 2012 / 1062 vom 23. November 2012 - VD Tribunal cantonal (2012)
RESTITUTION DU DÉLAI, OPPOSITION TARDIVE, CONTRAVENTION | 393 al. 1 let. a CPP (CH), 395 let. a CPP (CH), 94 CPP (CH)